PROFIL KETERAMPILAN GERAK DASAR LOKOMOTOR DI SEKOLAH DASAR NEGERI 12 PAGARUYUNG KABUPATEN TANAH DATAR - Fajri, Muhammad; Ibnu Andli Marta; Asnaldi, Arie; Handayani, Sri Gusti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to examine the profile of fundamental locomotor movement skills among students at Elementary School 12 Pagaruyung, Tanah Datar Regency. The research employed a quantitative descriptive approach, aiming to provide an empirical overview of students’ locomotor abilities without manipulating variables. The study was conducted at SDN 12 Pagaruyung, Kecamatan Tanjung Emas, during the 2025/2026 academic year. The population consisted of 183 students, with a sample of 29 second-grade students selected through purposive sampling, based on specific considerations determined by the researcher. The instrument used was the Test of Gross Motor Development-2 (TGMD-2), limited to the locomotor subtest. Data were analyzed using descriptive statistics with percentage formulas to classify skill levels. The findings revealed that only 1 student (3.4%) achieved locomotor skills within the interval class >41, categorized as “Very Good.” In the interval class 36–40, 6 students (20.7%) were classified as “Good.” The majority, 13 students (44.8%), fell into the interval class 30–35, categorized as “Moderate.” Meanwhile, 7 students (24.1%) were in the interval class 25–29, categorized as “Poor.” Finally, 2 students (6.9%) scored below 24, categorized as “Very Poor.” Overall, the results indicate that most students demonstrated locomotor skills at the moderate level, with only a small proportion achieving higher classifications. These findings highlight the need for systematic instruction and structured physical activities to enhance locomotor competence and support holistic student development.